O24 The five 'Es' of holistic care for adolescents and young adults with cancer. (20th March 2019) - Lea, Sarah; Gibson, Faith; Martins, Ana; Fern, Lorna; Whelan, Jeremy; Taylor, Rachel
Abstract : Introduction: One of the 'arts' of age-appropriate care for adolescents and young adults (AYA) with cancer is a holistic approach to delivering care, which relies on the knowledge, skills and attitudes of all healthcare professionals (HCP). Aim: The paper aims to describe the five 'Es' enabling holistic competence. Methods: Data were collected across four specialist AYA services (21 hospitals) in a multi-site case study; using semi-structured interviews with 29 AYA and 40 HCPs, focussed ethnography and observation (120 hours). Data were analysed through thematic and framework analysis. Results: HCP holistic competence was enabled by the five 'Es': Exposure to experience continuum: dependent on the AYA case load of the care setting. More contact with AYA facilitated knowledge in needs beyond clinical treatment. Enthusiasm: vital with smaller caseloads of AYA. Interest in the speciality heightened holistic knowledge, often created through leadership. Environment: a specialist environment to meet AYA psychosocial needs increased HCPs ability to support AYA holistically. Education: occurred on three levels: raising awareness of AYA needs, in–house education, and formal training in AYA care. Ethos: core to culture of care was a whole–team approach recognising individuality, empowering, and promoting normality for AYA. Discussion and conclusion: HCP holistic competence was dependent on the level of contact with AYA: a continuum from infrequent exposure to AYA, to substantial experience in specialist services. This contact level was related to the care environment (non-specialist or specialist) and together with enthusiasm for the speciality, was a key factor in the creation of a holistic, AYA-focussed ethos of care. Centralising AYA cancer services would increase the experience HCPs have of working with AYA, within age-appropriate environments of care, thus fostering an ethos of care sensitive to AYA holistic needs. Whether this impacts outcome will become evident in early 2019 when the results of BRIGHTLIGHT are released.